2015
DOI: 10.1007/s00702-015-1466-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered serum fatty acid composition in geriatric depression

Abstract: Fatty acids (FA), mainly polyunsaturated (PUFA) of n-3 or n-6 types, may influence neuropsychobiological processes. Decreased levels of n-3 PUFA have been shown to be related to major depression and supplementation of n-3 PUFA seems to contribute to improved depression treatment outcome. The profiles of serum FA profiles in patients with geriatric depression have not been thoroughly studied yet. The present study investigated the FA profiles of patients with geriatric depression and of mentally healthy elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…12 For example, a recent study revealed that total cholesterol and lowdensity lipoprotein (LDL) serum levels were related to severity of depression, 13 while another conducted on older subjects failed to find an association between cholesterol levels and depression. 14 Few results have been published regarding fatty acid composition and mood symptoms, which show a significant difference between healthy subjects and those affected by geriatric 15 or perinatal depression. 16 In the light of these considerations, the purpose of the present investigation is to examine the association between serum lipid profile and depressive symptoms in subjects affected by CKD.…”
Section: Introductionmentioning
confidence: 99%
“…12 For example, a recent study revealed that total cholesterol and lowdensity lipoprotein (LDL) serum levels were related to severity of depression, 13 while another conducted on older subjects failed to find an association between cholesterol levels and depression. 14 Few results have been published regarding fatty acid composition and mood symptoms, which show a significant difference between healthy subjects and those affected by geriatric 15 or perinatal depression. 16 In the light of these considerations, the purpose of the present investigation is to examine the association between serum lipid profile and depressive symptoms in subjects affected by CKD.…”
Section: Introductionmentioning
confidence: 99%